2022
DOI: 10.1002/ajp.23370
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of rectal and oral cultivable microbiota in wild and captive black lion tamarins (Leontopithecus chrysopygus, Mikan 1823)

Abstract: The black lion tamarin (Leontopithecus chrysopygus) is an endangered primate species, restricted to the Atlantic Forest fragments of São Paulo state, Brazil, with an estimated wild population of ~1600 individuals. Integrative studies between zoo (ex situ) and wild (in situ) animals are crucial to modern conservation programs. They can demonstrate a substantial impact with the One Health concept, an interdisciplinary research frontier regarding the relations between human, animal, and environmental health. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…They conclude that finding these trypanosomes in zoo‐housed primates is of great concern as they could potentially become involved in the transmission cycle of this parasite, with risks to other animals and humans. The final paper presented in this issue, Fatoretto et al (2022), compared the oral and rectal microbiota found in both wild and captive black lion tamarins. This study found that gram‐positive bacteria were more prominently found in wild black lion tamarins, gram‐negative bacteria were more prominent in captive black lion tamarins.…”
mentioning
confidence: 99%
“…They conclude that finding these trypanosomes in zoo‐housed primates is of great concern as they could potentially become involved in the transmission cycle of this parasite, with risks to other animals and humans. The final paper presented in this issue, Fatoretto et al (2022), compared the oral and rectal microbiota found in both wild and captive black lion tamarins. This study found that gram‐positive bacteria were more prominently found in wild black lion tamarins, gram‐negative bacteria were more prominent in captive black lion tamarins.…”
mentioning
confidence: 99%